1993
DOI: 10.1144/0041025
|View full text |Cite
|
Sign up to set email alerts
|

Late Paleocene to Miocene compression in the Faeroe–Rockall area

Abstract: Compressional structures are observed at several locations in the Faeroe-Rockall Area. One of these, the Wyville-Thomson Ridge Complex, is part of the Scotland Greenland Ridge which forms a barrier to the south-flowing deep cold arctic water from the Norwegian Sea. Interpretation of seismic multichannel reflection profiles suggests that the Wyville-Thomson Ridge Complex is the result of compression and that the Ymir Ridge and the Wyville-Thomson Ridge are ramp anticlines connected with a fault plane dipping to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 27 publications
4
97
0
Order By: Relevance
“…The reflection is characterized by being the strongest amplitude reflection below that of the sea bed, and by the rugose nature of its top surface. The top lava sequence 1 pick is heavily affected by the Eocene to Miocene compressional phases associated with changes in the spreading dynamics of the NE Atlantic (Boldreel & Andersen 1993), and the surface is faulted in much of the GFA-99 area. A characteristic feature of the top lava sequence 1 is the presence of thrust faults that pierce the surface and the presence of associated thrust-tip folds (e.g.…”
Section: A Lava Sequencementioning
confidence: 99%
“…The reflection is characterized by being the strongest amplitude reflection below that of the sea bed, and by the rugose nature of its top surface. The top lava sequence 1 pick is heavily affected by the Eocene to Miocene compressional phases associated with changes in the spreading dynamics of the NE Atlantic (Boldreel & Andersen 1993), and the surface is faulted in much of the GFA-99 area. A characteristic feature of the top lava sequence 1 is the presence of thrust faults that pierce the surface and the presence of associated thrust-tip folds (e.g.…”
Section: A Lava Sequencementioning
confidence: 99%
“…2b), and has a maximum fold amplitude of 3000 m and a bathymetric expression along its length. Boldreel & Andersen (1993 recognized PaleoceneEocene and Eocene -Oligocene compressive growth phases, and thinning and onlap in seismic reflection data suggest an enhanced phase of growth in the Mid-Miocene (Fig. 2b), as well as possible further growth during Pliocene to Recent times (Ritchie et al 2003;Johnson et al 2005;Stoker et al 2005a).…”
Section: Faroe-shetland Areamentioning
confidence: 97%
“…To the south of the Faroe Platform, the Munkagrunnur Ridge is a NNW-trending 135 km-long anticline with seabed expression (Boldreel & Andersen 1993;Johnson et al 2005;Ritchie et al 2008Ritchie et al , 2011. Boldreel & Andersen (1993) suggested that the ridge is part of a set of ramp-anticlines, along with the Ymir and Wyville Thomson ridges, which formed during the Late Paleocene -Eocene above a northwards-dipping crustal fault in response to seafloor spreading.…”
Section: Faroe-shetland Areamentioning
confidence: 99%
See 2 more Smart Citations